CA1 hippocampal neuronal responses to curry leaves extract treatment in rats subjected to chronic cerebral hypoperfusion : a behavioral and histopathological study - Azzubaidi, Marwan Saad; Mohd Noor, Noriah; Saxena, Anil Kumar; Al-Ani, Imad Matloub Dally; Ahmed, Qamar Uddin; Talib, Norlelawati A. (2013)
Curry leaves VIZ. Murraya koenigii leaves (MKL) extract was found to possess robust antioxidant and anticholinesterase activities. Its memory enhancing effect in preclinical studies has also been reported in an animal model of drug induced amnesia. Alzheimer’s disease (AD) in its vascular hypothesis has been linked to chronic decrease in cerebral blood flow when it attains significantly sub-threshold levels, a condition referred to as chronic cerebral hypoperfusion (CCH). The current study was designed to evaluate the possible neuroprotective potential of MKL methanolic extract in a two vessel occlusion (2VO) rat model of CCH. Rats were divided into memory and learning groups. Each of which was subdivided into sham control, untreated 2VO and MKL treated 2VO subgroups. Morris water maze test was implemented to assess the rats’ cognitive function at the 10th postoperative week. Harvested brain samples were processed for histopathological examination of CA1 hippocampal region using cresyl violet stain. Water maze test findings showed that MKL positively improved 2VO induced memory and learning impairments. However, this relatively improved performance for the MKL treated group was still significantly inferior to that of the control group. Additionally, MKL treated group exhibited insignificant difference in the number of viable hippocampal CA1 pyramidal neurons from that of untreated 2VO group, whereas both MKL treated and untreated 2VO groups showed significantly less viable neurons when compared with control group. It can be concluded that long-term oral MKL treatment did not exert neuroprotective effect to the CA1 hippocampal subfield in the experimental model of neurodegeneration that was induced through CCH.